Variations of geomagnetic H, D, and Z field intensities on quiet days at west african latitudes - Obiekezie, T. (D.Ghitu Institute of Electronic Engineering and Nanotechnologies, 2009)
In the framework of the French participation to the International Equatorial Electrojet